Leasing relations on the real estate market in Ukraine - Tugaj О.; Slipenchuk, O. (Ways to Improve Construction Efficiency, 2019)
The article is devoted to the study of modern trends in the formation of leasing relations in the real estate market in Ukraine, their legal and practical aspects.